Preceptorship Model for Nursing Undergraduate Students: A Systematic Review - Muhammad Irwan; Nur Isriani Najamuddin; Risnah; Musdalifah; Syamsiah Rauf; Andi Adriana Amal; Muthaharah (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: To find out the effectiveness of clinical education models for nursing undergraduate programs.Methods: From the PubMed, Science direct, Wiley online, and Secondary Search databases, 7 articles were obtained consisting of qualitative research that discussed the model of implementing preceptorship for nurses and undergraduate nursing students. The selection of research articles to be reviewed by establishing the inclusion and exclusion criteria then the process of searching for articles is synthesized into PRISMA flow diagram. Journal criticisms have been carried out using Qualitative CASP tools and Case-control. Results: Researches from 8 countries that have been published and can be generalized to where the average participant is described as a student undergraduate nursing, nursing staff and clinical facilitators / supervisors. This type of intervention is focused on various clinical education models for undergraduate nursing programs. The findings obtained regarding the effectiveness of the clinical education model for undergraduate nursing programs. This review literature proves that the clinical facilitator model (preceptrorship) is better than the educator model based on student perception and learning outcomes. Conclusion: This review literature proves that the clinical facilitator model (preceptrorship) is better than the standard educator model based on student perceptions and student learning outcomes themselves, it is proven that the preceptorship model provides greater involvement and learning environment compared to the standard facilitator model. All clinical education models show the advantages or disadvantages and limitations of each, however the potential student learning outcomes can be maximized if the model used is the results evaluated using systematic research.